2018
DOI: 10.3390/ijms19071848
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Activator of Nuclear Factor Kappa B (RANK) and Clinicopathological Variables in Endometrial Cancer: A Study at Protein and Gene Level

Abstract: The system integrated by the receptor activator of nuclear factor kappa B (RANK) and its ligand, RANKL, modulates the role of hormones in the genesis and progression of breast tumors. We investigated whether the expression of RANK was related with clinicopathological features of primary endometrial tumors. Immunohistochemistry was used in an endometrial cancer tissue array containing samples from 36 tumors. The amount of RANK mRNA was examined in a tissue scan cDNA array containing cDNA from 40 tumors. Normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 18 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…As a regulator of signal transduction, the nuclear factor-κB (NF-κB) protein complex is involved in various biological processes, including inflammation, immune response and apoptosis, and has received increasing attention in recent years (15,16). The NF-κB signaling pathway in mammals primarily involves the p65/p50 heteromer, which binds its inhibitory protein [inhibitor of NF-κB B (IκB) subunit IκBα], masking the nuclear translocation signal of NF-κB (17).…”
Section: Introductionmentioning
confidence: 99%
“…As a regulator of signal transduction, the nuclear factor-κB (NF-κB) protein complex is involved in various biological processes, including inflammation, immune response and apoptosis, and has received increasing attention in recent years (15,16). The NF-κB signaling pathway in mammals primarily involves the p65/p50 heteromer, which binds its inhibitory protein [inhibitor of NF-κB B (IκB) subunit IκBα], masking the nuclear translocation signal of NF-κB (17).…”
Section: Introductionmentioning
confidence: 99%
“…As a first step, it is important to determine whether RANK is expressed in the endometrium, and whether, as shown in the breast, it may serve as a prognostic indicator in endometrial cancer. More recently published findings have confirmed both premises, including increased RANK expression in parallel to tumor dedifferentiation [13]. Moreover, another study has shown that RANK expression increases in endometriosis, as an intermediate state between normal and malignant endometrium [14].…”
Section: Ovarian Steroids and Cancer: News On The Breast Questions Omentioning
confidence: 66%
“…Representative pictures were taken with an Olympus BX40 SC30 lens system (Olympus, Barcelona, Spain) and quantification of average integrated optical density (IOD) in the outlined areas performed through Image-Pro-Plus 6.0, as described. 4 To delineate endometrium from ovarian stroma, serial adjacent section of endometrioma RANK-stained slides underwent CD10 immunorecognition with a FLEX ready-to-use DAKO monoclonal antibody (clone 56C6; Dako, Glostrup, Denmark) in an automated Link 48 DAKO autostainer following manufacturer protocol The amount of RANK staining was expressed as a logarithmic function of the IOD (mean AE SD), and statistical analysis was performed with SPSS 24.0. Comparisons between group samples were made by ANOVA followed by a Tukey post hoc test.…”
Section: Methodsmentioning
confidence: 99%